Las acciones de Costa Rica ante los hechos en Palestina desde el 7 de octubre de 2023 - Johanning Solís, Javier (El Colegio de México A.C., 2024)
Costa Rica has embedded its own defense within international law. However, this has been called into question since events like the attacks on October 7, 2023, by Hamas and Israel’s subsequent attack on Gaza. Therefore, it is relevant to study Costa Rica’s responses and actions amidst the worsening humanitarian situation of the Palestinian population in general, and especially in the Gaza Strip. The disproportionality of Israel’s military actions has raised alarms and prompted a multitude of reactions internationally, among which one of the most significant is South Africa’s action of bringing a case against Israel for genocide before the International Court of Justice (ICJ).